(untitled) (Palíndromo, 2022)
This study addresses teacher education, with the aim of reflecting on education and technology in contemporary society, based on the method of historical-dialectical materialism. As a result, we realize that the educational area is undergoing neoliberal reforms since the 1990s in Latin America. These reforms are under business direction, transmitting values that legitimize dominant interests and maintain working class exploitation and expropriation relations. We conclude that the Common National Curriculum Base (BNCC), the reform of secondary education, remote education and the measures to cut public investment in health and education are signs of the disregard for the quality of training of the working classes. And that technology has become an instrument for submitting the workforce to an unlimited time, leading humanity to exhaustion.